Catheter-related bloodstream infection management in patients receiving home parenteral nutrition: An observational cohort study. (August 2022) - Gompelman, Michelle; Causevic, Erna; Bleeker-Rovers, Chantal P.; Wanten, Geert J.A.
Summary: Background and aims: Patients with intestinal failure receiving home parenteral nutrition (HPN) are susceptible to central-line associated bloodstream infections (CLABSIs), with crucial roles for adequate (empiric) antimicrobial therapy and effective catheter management strategies. Our aim was to link recent epidemiologic CLABSI data with clinical outcomes and to identify risk factors for therapeutic failure to decide on the safest and most accurate CLABSI management in patients receiving HPN. Methods: A retrospective observational cohort study was conducted. All data on CLABSIs (period 2010–2020) in adult patients receiving HPN were retrieved. The efficacy of attempted catheter salvage and empiric antimicrobial treatment (β-lactam antibiotics) in our center, with a low prevalence of methicillin-resistant staphylococci, was investigated. Multivariate cox-regression analysis was performed to identify risk factors for recurrent CLABSI. Results: 389 CLABSIs occurred in 149 patients. The overall infection rate was 0.64 per 1000 central venous catheter (CVC) days. Most CLABSIs were caused by Coagulase-negative staphylococci (37%). Attempted CVC salvage was successful in 70% of the cases. Empiric antimicrobial therapy was found to be adequate in only 47% of cases, mainly because of insufficient Coagulase-negative staphylococci coverage. According to the Cox model, patients with a replaced CVC had a 50% lower risk of a new CLABSI than patients with a retained (salvaged) CVC during follow-up (HR 0.50; 95% CI 0.35–0.72, P < 0.001). Conclusions: CVC salvage can be achieved in most CLABSI cases but seems associated with a shorter CLABSI-free survival. Importantly, based on our findings, a glycopeptide containing antibiotic treatment regimen will increase the likelihood of adequate empiric coverage.